Post-operative analgesia for major abdominal surgery and its effectiveness in a tertiary care hospital - Aliya Ahmed; Naveed Latif; Robyna Khan (Wolters Kluwer Medknow Publications, 2013)
Background: Post-operative pain is often inadequately treated. Optimal utilization of the available resources is essential for improving pain management. Aims: The aim of our study was to determine pain management strategies employed after major abdominal surgeries at our institute and their efficacy and safety. Settings and Design: Prospective observational study conducted at a tertiary care hospital. Materials and Methods: Patients undergoing elective major abdominal surgeries were included. Post-operative analgesic strategy, co-analgesics used, pain and sedation scores, motor block, nausea and vomiting were recorded and patient satisfaction was determined. Results: Data was collected on 100 patients. Epidural analgesia was used in 61, patient controlled intravenous analgesia (PCIA) in 25 and opioid infusion in 14 patients. Multimodal analgesia was employed in 98 patients. The level of epidural was between L1-L3 in 31, T10-L1 in 20 and T8-T10 in 10 patients. Pethidine was used in 80% of patients receiving PCIA. Patients with epidurals at T8-T10 had lower pain scores. Fifteen patients had motor block, 73% of which were with epidural at L1-L3. Fourteen patients complained of nausea. Ninety nine out of 100 patients were satisfied with their analgesia. Conclusion: Epidural, PCIA and opioid infusions are used for pain relief after major abdominal surgeries at our hospital. Although there is limited drug availability, regular assessments and appropriate dose adjustments by acute pain management service (APMS) and use of multimodal analgesia led to a high level of patient satisfaction. We recommend that feedback to the primary anesthesiologists by APMS is of utmost importance to enable improvement in practice.